26.5: View Angle Characteristics of LCD/OLED/miniLED/microLED Panels. (26th August 2021) - Liu, Luning; Feng, Xiaofan; Zheng, Zengqiang; Zhang, Shengsen; Geng, Hai; Zheng, Jiong
Abstract : The view angle characteristics refer to the changes in the luminance that occur with varying view directions which is defined as the luminance's view angle dependence (LVAD) in this paper. Recently the LVAD of OLED/LCD/miniLED/microLED panels attracts more attention. In this paper, the LVAD of OLED/LCD/mini LED/micro LED were measured and compared. For each panel, the LVAD of three gray levels and three colors at nine positions and four azimuth angles has been measured. The gray levels are 255/128/32, the colors are red (R), green (G), blue (B) and the azimuth angles are 0/90/180/270 degrees. It was found that the LVAD of OLED/miniLED/microLED changes a lot with colors except LCD panels. And the LVAD of all panels changes with the measurement azimuth angles. Gray levels will also affect the LVAD if different gray levels are with different spectra. Besides, OLED/LCD/miniLED panels exhibit the same LVAD at different positions.